Impact of ballast water on the health of workers of maritime transport vessels that sail in Peruvian waters - Fernández García, Miguel Ángel (2022)
This research has allowed us to observe the ballast water management conditions in our first port and its impact on the health of maritime vessel workers, appreciating the procedures of the on-board personnel. In this study it is observed if compliance with regulations and aspects that are evaluated and interpreted to understand the nature of the problem are considered, with respect to people and the core is the exposure due to ignorance or negligence, to propose the instruction of the personnel to prevent unfortunate events from occurring. That is the object of the study to analyze the conditions, both of vessels and of people with respect to this issue that today is an important cause of concern in people, referring to the management or handling of ballast water and that the present study described in the best possible way. The objective of the investigation was to appreciate the problem that the ballast water when being manipulated can cause damage to the health of the officers or crew of the vessels, especially in the ballasting operations, to achieve this, the following was used: Satisfaction survey, Knowledge of the Protocol and Observation of conditions, with these studies it was possible to understand the ballast water situation and the safety of the members of a vessel in this procedure, to carry out the study a qualitative correlational design has been used, in this way Objectively assess the damage they could cause, based on this the study serves as the basis for developing a proposal that improves this aspect of the safety and health of maritime vessel personnel in a substantive way.